# C3 logs questionWatch

This discussion is closed.
#1
Find, as natural logarithms, the root of the equation

2e^(x) + 3e^(-x) = 7
0

4 years ago
#2
(Original post by fan1597534862)
Find, as natural logarithms, the root of the equation

2e^(x) + 3e^(-x) = 7
e^(-x)[2e^(2x) + 3] = 7

--> 2e^(2x) + 3 = 7*(1/e^(-x))
= 7e^x

--> 2e^(2x) - 7e^x + 3 = 0

set A=e^x

--> 2A^2 - 7A + 3 = 0
--> 2A^2 - 6A - A + 3 = 0
--> (2A-1)(A-3) = 0 --> A=½ & A=3

--> e^x=½ --> x = ln(½) & e^x=3 --> x = ln3

Hope this helps.
0
X
new posts
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### University open days

• Cranfield University
Cranfield Forensic MSc Programme Open Day Postgraduate
Thu, 25 Apr '19
• University of the Arts London
Open day: MA Footwear and MA Fashion Artefact Postgraduate
Thu, 25 Apr '19
• Cardiff Metropolitan University
Sat, 27 Apr '19

### Poll

Join the discussion

#### Have you registered to vote?

Yes! (125)
39.56%
No - but I will (17)
5.38%
No - I don't want to (20)
6.33%
No - I can't vote (<18, not in UK, etc) (154)
48.73%